Relationship between the kinetics and kinematics of a unilateral horizontal drop jump to sprint performance - Jonsson Holm, D.; Stalbom, M.; Keogh, J. W. L.; Cronin, J. (The Journal of Strength and Conditioning Research, 2008)
The aim of this study was to investigate the relationship between the kinematics and kinetics of a single-leg horizontal drop jump (SLDJ) to sprint performance. Twenty regional-level male team-sport athletes gave informed consent to participate in this study. All subjects performed a series of 25-m sprints (measured by dual-beam infrared timing lights) and SLDJ (with both legs) in randomized block order during the same testing session. The SLDJ required the subjects to step downwards off a 20-cm box, land on the force plate (operating at 500 Hz) with the specified foot, and jump for maximal horizontal distance while minimizing ground-contact time. Jump distance, particularly when normalized to a subject's height, was the strongest correlate to sprinting time for all three (5, 10, and 25 m) distances (-0.44 < r < -0.65). Multiple linear regression analyses indicated that the SLDJ could account for a high level of variance in sprint time (0.49 < r2 < 0.68) and that these predictions had a relatively low standard error of estimate (0.02-0.10 seconds). These results further support the contention that jump (particularly horizontal) and sprint ability for short distances are highly related. Whereas practitioners should consider using more horizontal than vertical jumps in the training and testing of most team-sport athletes, additional research into the kinetic determinants of jumping and sprinting may allow a more specific and individualized exercise prescription for improving certain aspects of sprinting such as step length or step rate or the vertical vs. horizontal contributions to propulsion.